Reflexiones desde la mirada de la terapia Gestalt sobre la danza urbana y la corporalidad (2021)
This article presents some of the results of the research “Appreciation of the bodily experience in hip-hop dance from the concepts of Gestalt therapy: a pragmatic and contextualist approach” to obtain the degree of Psychologist at the Universidad Santo Tomás. The reflections proposed by this work aim to highlight the importance of a holistic view of the human being as a whole body-mind, and the integrated work that psychotherapy and health sciences should seek. For this, urban dance is highlighted as a bodily experience through the participants of our research and other studies carried out, which enables the integration of the bodily dimension of human existence to the psychological view of human phenomena, in order to recognize urban dance as a potential tool for a bodily psychotherapy work such as Gestalt therapy.